Activation transport under quantum Hall regime in HgTe-based heterostructure - Gudina, S.V.; Neverov, V.N.; Novik, E.G.; Ilchenko, E.V.; Harus, G.I.; Shelushinina, N.G.; Podgornykh, S.M.; Yakunin, M.V.; Mikhailov, N.N.; Dvoretsky, S.A. (Физика низких температур, 2017)
We have measured the temperature (2.9 K < T < 50 K) and magnetic field (0 T < B < 9 T) dependences of longitudinal and Hall resistivities for HgCdTe/HgTe/HgCdTe system with HgTe quantum well width of 20.3 nm. The activation analysis of the experimental magnetoresistivity traces has been used as a quantitative tool to probe inter-Landau level distances. The activation energies were determined from the temperature dependence of the longitudinal resistivity in the regions of quantized Hall plateaus (for the filling factors ν of 1, 2 and 3) and the indications of the large values of the g factor ≅ 30–75 were found.